Speech enhancement methods based on perceptual wavelet filterbank - Shao, Yu (2010)
The extraction and synthesis of quality speech is of utmost importance for a diversity of digital speech processing applications ranging from mobile communication systems, digital hearing aids, quality enhancement of old records, speech recognition systems to hands-free car kits. Most speech processing systems that work well in underrated noise condition degrade drastically in practical noisy environments. Noise induced aggravation causes inaccurate information exchange and lowers the quality of speech. An overwhelming number of methods have been developed over years to address the speech enhancement problem. This thesis investigates into versatile speech enhancement algorithms in order to increase the intelligibility of speech and reduce auditory fatigue.